Use of adjuvants to increase efficacy of PRRSV modified live vaccines - Li, Xiangdong (Kansas State University, 2014)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically important swine diseases worldwide that leads to severe reproductive failure in sows and high mortality in young pigs. Vaccination is currently the most effective way to control this disease. The protection ability provided by vaccines however is limited due to the large diversity of field PRRSV strains. In chapter 2, we compared immune responses induced by vaccination and/or PRRSV infection by using IngelVac® Modified Live PRRSV vaccine (MLV), its parental strain VR-2332, and the heterologous KS-06 strain. Our results showed that MLV provide complete protection to homologous virus and partial protection to heterologous challenge. The protection was associated with the levels of PRRSV neutralizing antibodies at the time of challenge. Besides developing new vaccines to combat PRRSV, adjuvants have been applied to PRRSV MLV vaccines to induce vaccination-mediated cross-protection against genetically dissimilar PRRSV strains. In chapter 3, we demonstrated that a commercial MontanideTM Gel01ST adjuvant provides enhanced protection to homologous PRRSV infection by regulating the production of PRRSV-specific antibodies. In chapter 4, we tested a novel peptide nanofiber hydrogel acting as a potent adjuvant for PRRSV MLV vaccines. We found that the hydrogel adjuvant enhanced vaccine efficacy by developing of higher titers of neutralizing antibodies and stronger IFN-γ cellular immune responses. Chinese highly pathogenic PRRSV (HP-PRRSV) variants were isolated in 2006 and they belong to genotype 2 of PRRSV. Compared with classic PRRSV, HP-PRRSV is characterized by robust proliferation ability and high morbidity/mortality with all ages of pigs. In chapter 5, we compared the difference of immune responses elicited by HV-PRRSV, a Chinese HP-PRRSV, and a US virulent strain of PRRSV NADC-20. Traditional PRRSV MLV vaccines developed in US offer no protection to HP-PRRSV. Vaccines specific to HP-PRRSV strains available in China provide protection to HP-PRRSV. In chapter 6, we demonstrated that pigs challenged with US NADC-20 strain were protected by vaccination with Chinese MLV HP-PRRSV vaccines. The availability of Chinese HP-PRRSV vaccines in North America may act to increase the preparedness of possible transmission of HP-PRRSV to North America.
Keywords: Vaccine; Adjuvant; PRRSV; Veterinary Medicine (0778)